Analisis Pengaruh Pengangguran, Indeks Pembangunan Manusia, dan Upah terhadap Kemiskinan di Karesidenan Surabaya Tahun 2015-2020 - Nurul Pratiwi; Eni Setyowati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Poverty is the one of the problems in a complex and multidimensional economy, so the solution is to reduce the level of poverty. This study aims to estimate the influence of the unemployment, human development index (HDI) and wages on poverty in Surabaya Residency in 2015-2020 used panel data regression. The results of this selected research using Random Effect (REM) approach, show that the unemployment variable has a positive effect on poverty while the HDI has a negative effect on poverty. Meanwhile, wage variable has no effect on poverty.